Effect of commercial mouthwashes on the corrosion resistance of Ti-10Mo experimental alloy - Alves Rezende, Maria Cristina Rosifini; Rosifini Alves, Ana Paula; Norberto Codaro, Eduardo; Matsumoto Dutra, Conceicao Aparecida (Springer, 2007)
The purpose of this work was to evaluate the effect of three commercial mouthwashes on the corrosion resistance of Ti-10Mo experimental alloy. Experiments were made at 37.0 +/- 0.5 degrees C in a conventional three-compartment double wall glass cell containing commercial mouthwashes. Three mouthwashes with different active ingredients were tested: ( I) 0.05% sodium fluoride + 0.03% triclosan; (II) 0.5 g/l cetylpyridinium chloride + 0.05% sodium fluoride; (III) 0.12% chlorohexidine digluconate. The assessment of the individual effect of active ingredients was studied by using 0.05% sodium fluoride. Commercially pure titanium (CP Ti) was used as control. Microstructures from Ti-10Mo experimental alloy and CP Ti were also evaluated using optical microscopy. Ti-10Mo as-cast alloy shows the typical rapidly cooled dendrites microstructure (beta phase) while CP Ti has exhibited a metastable martensitic microstructure. Electrochemical behavior of dental materials here studied was more affected by mouthwash type than by Ti alloy composition or microstructure. In both alloys passivation phenomenon was observed. This process may be mainly related to Ti oxides or other Ti species present in spontaneously formed film. Small differences in passive current densities values may be connected with changes in film porosity and thickness. Protective characteristics of this passive film are lower in 0.05% sodium fluoride + 0.03% triclosan mouthwash than in the other two mouthwashes tested.